Analisa Pendapatan Usaha Tani Pisang Kepok di Desa Bloro Kecamatan Nita Kabupaten Sikka - Selfianus Selfianus (Agriculture - Jurnal Ilmu Pertanian, 2025)
A study was conducted in Bloro Village, Nita District, Sikka Regency. The purpose of this study was to determine how much income the respondent farmers received from kepok banana farming and to determine how much relative profit they received from kepok banana farming in Bloro Village, Nita District, Sikka Regency. The results showed that the average income of respondent farmers was Rp. 722,355, with the lowest income being Rp. 248,500, and the highest income being Rp. 1,692,500. The income obtained from kepok banana farming was only sufficient for farmers' household consumption while other needs such as education and health were obtained from other farming businesses. From the analysis results, it was found that the R/C Ratio of kepok banana farming in Bloro Village was 5.5. Based on the criteria, the kepok banana farming R/C Ratio of 5.5, which means greater than 1, means that kepok banana farming in Bloro Village is said to be feasible to be cultivated.